5‐2‐1‐0 Lifestyle risk factors predict obesity in Millennials. Issue 3 (25th March 2019) - Kerrigan, Dennis J.; Rukstalis, Margaret R.; Ehrman, Jonathan K.; Keteyian, Steven J.; She, Ruicong; Alexander, Gwen L.
Abstract : The Making Effective Nutritional Choices Generation Y (MENU GenY) study is a web‐based intervention trial aimed at improving food choices in those aged 21‐30 years. We report baseline levels of the 5‐2‐1‐0 healthy lifestyle patterns to predict a body mass index (BMI) ≥30 vs <30 kg m −2 . Overall, 1674 young adults (69% female) from two large health systems enroled and completed an online survey asking questions about lifestyle habits. A multivariable binary logistic regression model was utilized to predict a BMI ≥30 while controlling for known predictors of obesity. Consuming >3 daily servings of fruits/vegetables (odds ratio, OR = 0.90, 95% confidence interval, CI = 0.81, 0.99), and reporting >2.5 hours/week of vigorous physical activity (OR = 0.93, 95% CI = 0.89‐0.96, P < 0.001) was associated with a BMI <30. Conversely, time sitting (OR = 1.07, 95% CI = 1.04, 1.11) and consuming sugar‐sweetened beverages (OR = 1.08, 95% CI = 1.00, 1.15) were related to a BMI ≥30. In this cohort of 20‐30‐year‐olds, we observed a consistent relationship between obesity and the 5‐2‐1‐0 healthy lifestyle patterns previously reported among children and adolescents.